2006
DOI: 10.1007/s00214-006-0203-4
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to shed light on molecular mechanisms in biological processes

Abstract: Computational approaches based on Molecular Dynamics simulations, Quantum Mechanical methods and 3D Quantitative Structure-Activity Relationships were employed by computational chemistry groups at the University of Milano-Bicocca to study biological processes at the molecular level. The paper reports the methodologies adopted and the results obtained on Aryl hydrocarbon Receptor and homologous PAS proteins mechanisms, the properties of prion protein peptides, the reaction pathway of hydrogenase and peroxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 162 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Similar methodologies have been also used in literature very recently to model the protein‐ligand interaction so as to complement experimental data and, concomitantly, inspire new experimental tests. 20–26 Finally, for corroborating the obtained results, we have also employed the MMFF94x ForceField (Merck FF) on the best energy scored binding modes in order to evaluate possible significant variations in the protein ligand interaction upon FF switching 27. CHARMM22 docking poses were substantially confirmed both from a structural and an energy standpoint.…”
Section: Methodsmentioning
confidence: 73%
“…Similar methodologies have been also used in literature very recently to model the protein‐ligand interaction so as to complement experimental data and, concomitantly, inspire new experimental tests. 20–26 Finally, for corroborating the obtained results, we have also employed the MMFF94x ForceField (Merck FF) on the best energy scored binding modes in order to evaluate possible significant variations in the protein ligand interaction upon FF switching 27. CHARMM22 docking poses were substantially confirmed both from a structural and an energy standpoint.…”
Section: Methodsmentioning
confidence: 73%
“…Early EPR studies clearly demonstrated that Cu(II) binding to the PrP(92−96) fragment (with sequence GGGTH) involves the His96 imidazole and deprotonated amide groups from the preceding Thr and Gly residues . Cu(II) binding at the His96 site is highly pH-dependent, and it can adopt a 3N1O or 4N equatorial coordination mode, depending on pH. , Regarding Cu(II) binding to His111, there is consensus that Lys residues are not involved in Cu binding, , and that Cu(II) coordinates to the His imidazole ring and to a number of deprotonated amide groups from the backbone (one to three). ,,,,, However, there is controversy regarding the participation of the Met residues: based on circular dichroism (CD), EPR and NMR experiments it has been reported that no sulfur atoms participate in Cu(II) binding, ,, while other groups propose Met coordination in the equatorial position, based on CD, EPR and X-ray absorption spectroscopy. ,, Thus, the different proposals for equatorial coordination modes of Cu(II) bound to His111 at physiological pH include the following: 3NO with or without two axial waters, 4N, ,, 3NS, 2N2S and 2NSO with the participation of both Met109 and Met112 residues. ,, Unfortunately the investigation of Cu(II) binding to His111 using electronic structure calculations has been scarce, and the only reports of electronic calculations for this site used overly simplified models for the amino acids that may participate in the coordination of the metal ion. , Understanding Cu(II) binding to His111 is important, as this section of the protein is highly conserved in mammalian prion proteins, and it has been identified as a key region in the structural modifications associated with the conversion of PrP C to PrP Sc , both experimentally and by molecular dynamics . Moreover, the PrP(106−126) fragment that contains His111 is highly fibrillogenic and neurotoxic in vitro, it is protease resistant, it produces reactive oxygen species, and its Cu(II) complex has been shown to be redox active at physiological pH …”
Section: Introductionmentioning
confidence: 99%
“…64,66 Understanding Cu(II) binding to His111 is important, as this section of the protein is highly conserved in mammalian prion proteins, 67 and it has been identified as a key region in the structural modifications associated with the conversion of PrP C to PrP Sc , both experimentally 68 and by molecular dynamics. 69 Moreover, the PrP(106-126) fragment that contains His111 is highly fibrillogenic and neurotoxic in vitro, 70 it is protease resistant, 71 it produces reactive oxygen species, 72 and its Cu(II) complex has been shown to be redox active at physiological pH. 50 In this study we use different spectroscopic techniques (absorption, CD and EPR) in combination with electronic structure calculations to elucidate the coordination modes involved in Cu(II) binding to His111 in the PrP(106-115) fragment.…”
Section: Introductionmentioning
confidence: 99%
“…5 Common computational techniques to study the structure and reactivity of enzymes are molecular dynamics (MD) simulations and transition state calculations via combined quantum mechanics (QM)-molecular mechanics (MM) or via a full QM approach. 3,[6][7][8][9][10][11][12] These methods focus on finding reaction paths by the computation of activation energies. A computationally less demanding method uses the reactivity descriptors founded in conceptual density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…For larger systems such as proteins, zeolites, fullerenes, and nanotubes, not only are trends often well reproduced but also sometimes amazing agreement between theory and experimental data is obtained . Common computational techniques to study the structure and reactivity of enzymes are molecular dynamics (MD) simulations and transition state calculations via combined quantum mechanics (QM)−molecular mechanics (MM) or via a full QM approach. , These methods focus on finding reaction paths by the computation of activation energies. A computationally less demanding method uses the reactivity descriptors founded in conceptual density functional theory (DFT). , This method describes the preferred reaction energetics and thus kinetics in terms of the properties of the reagents in the ground state and is a successful tool to gain insight into how enzymes work.…”
Section: Introductionmentioning
confidence: 99%